AOI‐cast in distributed virtual environments: an approach based on delay tolerant reverse compass routing. (20th December 2012) - Ricci, Laura; Genovali, Luca; Carlini, Emanuele; Coppola, Massimo; Smari, Waleed; Fiore, Sandro; Trinitis, Carsten; Ranjan, Rajiv; Buyya, Rajkumar; Nepal, Surya; Georgakopulos, Dimitrios
Summary This paper presents a novel Area Of Interest (AOI)‐cast algorithm for distributed virtual environments targeted to Delaunay‐based P2P overlays. The algorithm exploits the mathematical properties of Delaunay triangulations to build a spanning tree supporting the notification of the events generated by a peer to the other ones located in its AOI. The spanning tree is computed by the reversing compass routing, a routing algorithm proposed for geometric networks. Our approach presents a set of novel features. First, it requires only the knowledge of the peer's neighbors, so that the amount of traffic load on the P2P overlay is minimized. Second, we prove that, for circular shaped AOI, the algorithm builds a spanning tree covering all and only the peers of the AOI. Finally, our approach takes into account the possible inconsistencies among the local views of the peers, because the network latency, by introducing a tolerance threshold in the reverse compass routing. We present a set of simulations considering both synthetic data and real data traces taken from a real multiplayer game, which show the effectiveness of our proposal. Copyright © 2012 John Wiley & Sons, Ltd.